Venezuela Before Chávez : Anatomy of an Economic Collapse - Rodríguez, Francisco, 1970-; Hausmann, Ricardo (Book collections on Project MUSE., 2014)
"A collection of essays that explore the collapse of economic growth in Venezuela since the 1970s. Essays discuss the relevance of public investment, labor markets, fiscal policy, institutions, politics, and values"--Provided by publisher